Does the Ethnic Difference Affect the Pharmacokinetics of Favipiravir? A Pharmacokinetic Study in Healthy Egyptian Volunteers and Development of Level C In-vitro In-vivo Correlation - Bendas, Ehab R.; Rezk, Mamdouh R.; Badr, Kamal A. (Drug Research, 2023)
Favipiravir is an antiviral drug used to treat influenza and is also being investigated for the treatment of SARS-CoV-2. Its pharmacokinetic profile varies depending on ethnic group. The present research examines the pharmacokinetic features of favipiravir in healthy male Egyptian volunteers. Another goal of this research is to determine the optimum dissolution testing conditions for immediate release tablets. In vitro dissolution testing was investigated for favipiravir tablets in three different pH media. The pharmacokinetic features of favipiravir were examined in 27 healthy male Egyptian volunteers. The parameter “AUC0-t” vs. percent dissolved was used to develop level C in vitro in vivo correlation (IVIVC) to set the optimum dissolution medium to achieve accurate dissolution profile for favipiravir (IR) tablets. The in vitro release results revealed significant difference among the three different dissolution media. The Pk parameters of twenty-seven human subjects showed mean value of Cpmax of 5966.45 ng/mL at median tmax of 0.75 h with AUC0-∞ equals 13325.54 ng.h/mL, showing half-life of 1.25 h. Level C IVIVC was developed successfully. It was concluded that Egyptian volunteers had comparable Pk values to American and Caucasian volunteers, however they were considerably different from Japanese subjects. AUC0-t vs. % dissolved was used to develop level C IVIVC to set the optimum dissolution medium. Phosphate buffer medium (pH 6.8) was found to be the optimum dissolution medium for in vitro dissolution testing for Favipiravir IR tablets.
Keywords: favipiravir; pharmacokinetics; in vitro In vivo correlation (IVIVC); ethnic effect.